Low social mobility in Bolivia: Causes and consequences for development - Lykke E. Andersen (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2001)
This paper investigates social mobility in Bolivia. It is an issue of high policy relevance as the degree of social mobility can have strong implications for both poverty reducation and long-run growth. Regressions based on household survey data show that social mobility is very low in Bolivia, even by Latin American standards. This is mainly caused by an inadequate public education system, a high degree of assortative mating, and insufficient rural-urban migration. As a consequence, poverty tends to be fairly persistent, with many families remaining poor year after year and generation after generation. In addition, low social mobility implies an inefficient use of innate talent as well as poor incentives for work and study. This prevents the Bolivian economy from reaching its potential growth rates. The paper provides several recommendations for policies that could help increase social mobility, thereby reducing poverty and increasing long-run growth.
Keywords: E60; I32; J12; J13; 330; Social Mobility; Economic Growth; Public Policy; Bolivia; Soziale Mobilität; Armut; Bildungswesen; Familienökonomik; Sozialer Status; Urbanisierung; Wirtschaftswachstum; Schätzung; Bolivien